A multi-agent cell-based model for wound contraction - Boon, W.M.; Koppenol, D.C.; Vermolen, F.J. (Journal of biomechanics, 2016)
A mathematical model for wound contraction is presented. The model is based on a cell-based formalism where fibroblasts, myofibroblasts and the immune reaction are taken into account. The model is used to simulate contraction of a wound using point forces on the cell boundary and it also determines the orientation of collagen after restoration of the damage. The paper presents the mathematical model in terms of the equations and assumptions, as well as some implications of the modelling. The present model predicts that the amount of final contraction is larger if the migration velocity of the leukocytes is larger and hence it is important that the immune system functions well to prevent contractures. Further, the present model is the first cell-based model that combines the immune system to final contractions.